1980
DOI: 10.4141/cjas80-030
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation and Utilization of Endogenous Urea in the Gastrointestinal Tract of Ruminants: A Review

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
154
3
5

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(173 citation statements)
references
References 10 publications
11
154
3
5
Order By: Relevance
“…It is also possible that tannins might decrease the entry rate of urea through the digestive tract. In conventional diets, EUN follows an opposite behaviour of MFN (37) , which might be attributable to urea recycling to the large intestine being enhanced by increasing hindgut fermentation with increasing NI (43,47) and increased concentrations of ammonia in the rumen (38) . The metabolisable protein requirement of sheep estimated from total basal N excretion i.e.…”
Section: Endogenous Nitrogen Lossesmentioning
confidence: 96%
See 1 more Smart Citation
“…It is also possible that tannins might decrease the entry rate of urea through the digestive tract. In conventional diets, EUN follows an opposite behaviour of MFN (37) , which might be attributable to urea recycling to the large intestine being enhanced by increasing hindgut fermentation with increasing NI (43,47) and increased concentrations of ammonia in the rumen (38) . The metabolisable protein requirement of sheep estimated from total basal N excretion i.e.…”
Section: Endogenous Nitrogen Lossesmentioning
confidence: 96%
“…In ruminants, a number of factors such as intakes of N, DM and digestible OM, ammonia concentration in the rumen and dietary NDF concentration influence the extent of urea N recycling to the gastrointestinal tract and MFN excretion. Kennedy & Milligan (38) proposed that urea recycling to the rumen increases when digestible OM intake increases and/or ruminal ammonia concentration decreases. Giraldez et al (37) clearly demonstrated that MFN increased quadratically from 153 to 280 mg/kg W 0·75 with increasing levels of digestible OM intake by sheep, which had been explained due to increased N entry to the gastrointestinal tract.…”
Section: Endogenous Nitrogen Lossesmentioning
confidence: 99%
“…In ruminants, significant amounts of urea formed in the liver can be transferred to the rumen (Kowalczyk et al, 1975a,b;Harmeyer and Martens, 1980;Kennedy and Milligan, 1980). Urea is then hydrolysed in the rumen (Gibbons and McKarthy, 1957) and the resulting ammonia is utilized by rumen bacteria as an important source of nitrogen for protein synthesis (Gärtner et al, 1961;Virtanen, 1964;Bunting et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Urea N recycling and assimilation by ruminal microbes are influenced by dietary and ruminal factors, and intakes of CP and digestible organic matter (OM) are major factors (Harmeyer and Martens, 1980;Kennedy and Milligan, 1980). A better understanding of the relationships between dietary factors and urea kinetics and microbial usage of recycled urea would allow for a more accurate estimation of N supply and N requirements by current feeding models.…”
mentioning
confidence: 99%
“…Ruminal NH 3 concentration, DOM and PUN concentration are the principal factors affecting urea recycling from blood to the lumen of the GIT (Kennedy and Milligan, 1980). Ruminal concentrations of NH 3 and OM digestion tend to be inversely related to each other, whereas GER is negatively related to ruminal NH 3 concentration, and positively related to PUN concentration.…”
mentioning
confidence: 99%